2005
DOI: 10.1590/s0004-282x2005000100026
|View full text |Cite
|
Sign up to set email alerts
|

Dificuldades diagnósticas na atrofia muscular espinhal

Abstract: RESUMO -Objetivo:Descrever o perfil clínico e laboratorial de pacientes com atrofia muscular espinhal (AME) com deleção no gene da proteína sobrevivência do neurônio motor (SMN). Método: Estudo descritivo de uma série de casos confirmados pela presença da deleção no gene SMN. Determinação da freqüência da positividade dos critérios clínicos e laboratoriais revisados. R e s u l t a d o s : Foram incluídos no estudo 22 casos. Em todos havia paresia simétrica, sendo a localização difusa predominante nos casos de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
1
4
0
7
Order By: Relevance
“…This small amount of muscle mass corroborates the clinical profile of weakness observed in SMA patients [1][2][3][4]6,8 . A recent Brazilian study 27 reported that 90% of the patients exhibited severe depletion of muscle reserve, in agreement with our results.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This small amount of muscle mass corroborates the clinical profile of weakness observed in SMA patients [1][2][3][4]6,8 . A recent Brazilian study 27 reported that 90% of the patients exhibited severe depletion of muscle reserve, in agreement with our results.…”
Section: Discussionsupporting
confidence: 83%
“…Spinal muscular atrophy (SMA) is a recessive, autosomal neuromuscular disease characterized by degeneration of anterior horn spinal cord motor cells and brain stem neurons [1][2][3][4][5] . It is classified by disease severity and the age at on set of symptoms, namely type I for the most severe cases and type IV for those presenting few complications 1,3,[6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Atrofia Muscular Espinhal (AME) faz parte de um grupo de doenças genéticas raras, de herança autossômica recessiva, caracterizada por degeneração dos neurônios motores da medula espinhal com incidência de 1 em 10.000 crianças nascidas vivas 1,2 . É classificada clinicamente em quatro tipos: severa (tipo I) ou Síndrome de Werdnig-Hoffman, intermediária (tipo II), branda (tipo III) e a do tipo IV que ocorre na fase adulta 3 .…”
Section: Introductionunclassified
“…1 The frequency of carriers (heterozygotes) is one in 40 to 60 people. 2 This disease is caused by a homozygous mutation or deletion of the survival motor neuron gene 1 (SMN 1 ), which should be located in the telomeric region of chromosome 5q13.…”
Section: Introductionmentioning
confidence: 99%